2020
DOI: 10.1159/000505369
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Methodology Used on Captive Subjects for Estimating Gut Passage Time in Wild Monkeys

Abstract: Gut passage time of food has consequences for primate digestive strategies, which subsequently affect seed dispersal. Seed dispersal models are critical in understanding plant population and community dynamics through estimation of seed dispersal distances, combining movement data with gut passage times. Thus, developing methods to collect in situ data on gut passage time are of great importance. Here we present a first attempt to develop an in situ study of gut passage time in an arboreal forest guenon, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…DRTs are reported to directly impact food digestibility, which probably depends on the gut volumes and food intakes of animals [31]. A number of studies have shown that DRTs are quite different among diverse animals; the DRT of monkeys was found to be 16-25 h [32], that of tortoises was 6-28 days [13], that of frugivorous birds was 15-45 minutes [33], and those of ruminants including cattle [34], elands [35] and horses [36] were generally 70-90 h, 45-70 h and 25-35 h, respectively. In this study, feeding experiments were conducted to examine the effects of age and food type on food intake rates and DRTs using captive T. roborowskii specimens.…”
Section: Retention Timementioning
confidence: 99%
“…DRTs are reported to directly impact food digestibility, which probably depends on the gut volumes and food intakes of animals [31]. A number of studies have shown that DRTs are quite different among diverse animals; the DRT of monkeys was found to be 16-25 h [32], that of tortoises was 6-28 days [13], that of frugivorous birds was 15-45 minutes [33], and those of ruminants including cattle [34], elands [35] and horses [36] were generally 70-90 h, 45-70 h and 25-35 h, respectively. In this study, feeding experiments were conducted to examine the effects of age and food type on food intake rates and DRTs using captive T. roborowskii specimens.…”
Section: Retention Timementioning
confidence: 99%